2021
DOI: 10.1186/s12935-021-02057-w
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation: driver of lymph node metastasis

Abstract: Fatty acid oxidation (FAO) is the emerging hallmark of cancer metabolism because certain tumor cells preferentially utilize fatty acids for energy. Lymph node metastasis, the most common way of tumor metastasis, is much indispensable for grasping tumor progression, formulating therapy measure and evaluating tumor prognosis. There is a plethora of studies showing different ways how tumor cells metastasize to the lymph nodes, but the role of FAO in lymph node metastasis remains largely unknown. Here, we summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 122 publications
(136 reference statements)
1
30
0
Order By: Relevance
“…A recent research work has shown that D-fructose 6-phosphate associated with PFKP may be a prognostic factor for lung cancer (Ganapathy-Kanniappan, 2020). In addition, several studies have suggested that fatty acid oxidation is abnormal in lung cancer cells, and FAO may regulate immune suppression through enabling lymph node metastasis formation (Liu et al, 2020;Li et al, 2021). In our study, we found that KD-FDX1 cells have higher L-palmitoylcarnitine and acylcarnitine levels at the same arachidonic acid (20:4) concentration.…”
Section: Discussionsupporting
confidence: 59%
“…A recent research work has shown that D-fructose 6-phosphate associated with PFKP may be a prognostic factor for lung cancer (Ganapathy-Kanniappan, 2020). In addition, several studies have suggested that fatty acid oxidation is abnormal in lung cancer cells, and FAO may regulate immune suppression through enabling lymph node metastasis formation (Liu et al, 2020;Li et al, 2021). In our study, we found that KD-FDX1 cells have higher L-palmitoylcarnitine and acylcarnitine levels at the same arachidonic acid (20:4) concentration.…”
Section: Discussionsupporting
confidence: 59%
“…LNs are lipid-rich tissues and cancer cells need to utilize lipids to colonize and survive in LNs. FAO is an important way for lipid utilization and is now gradually recognized as a critical driver of LNM (14). Previous studies have reported that increased FAO is involved in enhancing GC cell stemness, chemotherapyresistance and anoikis resistance for omental metastasis (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…To form metastasis in LNs, cancer cells must undergo metabolic reprogramming to successfully colonize and survive in an unfavorable microenvironment. Due to the lipid-rich property of LNs, the metabolic adaption of lymphatic metastatic cancer cells is more likely associated with fatty acid metabolism ( 14 ). It has been demonstrated that melanoma cells formed LNM depending on fatty acid oxidation (FAO) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other subsets of CD4 + T cells, Treg cells preferentially rely on FAO as a source of energy [9]. FAO is a multistep process that involves the beta‐oxidation of fatty acids in the mitochondria to produce acetyl‐CoA [31]. Several studies have shown that the regulators of FAO process can influence the differentiation of Treg cells.…”
Section: Discussionmentioning
confidence: 99%